CatArithm solving cryptarithmetic puzzle using CSO algorithm - Colibao, Floricel G. (2011)
Cryptarithmetic is a genre of mathematical puzzle which aims to assign digits to letters in order to come up with a meaningful and correct arithmetic operation. It is an interesting instance of a Constraint Satisfaction Problem (CSP) for which different algorithms had been implemented in finding for its optimal solution. As CSP, it involves a set of variables which are the unique letters, a finite set of possible values which are represented by the digits and number of constraints which need to be satisfied in searching for the optimal solution. This paper presents an application of Cat Swarm Optimization (CSO) in solving Cryptarithmetic puzzles. Experiment results illustrate the effectiveness of CSO in finding for the optimal solution of the said problem within a reasonable time. This study also shows that CSO compared to Genetic Algorithm (GA) requires lesser number of solutions to explore in the solution space to find the optimal solution. Moreover, CSO showed a satisfactory performance compared to Parallel Genetic Algorithm (PGA).
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.
Keywords: Cryptarithmetic; Constraint Satisfaction Problem; Cat Swarm Optimization